HUBUNGAN HBA1C DENGAN MIKROALBUMIN URIN PADA PASIEN DIABETES MELLITUS TIPE 2 DI PROLANIS KLINIK SEHAT SETIA BREBES - Muhammad Maksum Al-Rasyid; Endang Widhiyastuti (UNIVERSITAS BHAMADA SLAWI, 2023)
Diabetes mellitus is the main cause of all diseases. The prevalence of diabetes mellitus cases inCentral Java Province in 2019 was 652,822 cases. Cases in Brebes Regency are quite high with18,724 patients. Diabetes mellitus increases constantly if it is not treated properly and will lead tocomplications. The most frequent complication is causing a decrease in kidney function which ischaracterized by albuminuria. Prolanis aims to prevent complications due to diabetes mellitus.Monitoring blood sugar and urine microalbumin levels is very important in order to control thepatient's condition. Sugar levels are measured using HbA1c examination, because it is more stableand a specific marker for complications of diabetes mellitus. The purpose of this study was todetermine the relationship between HbA1c levels in the blood and urine microalbumin levels inpatients with type 2 diabetes mellitus at the Prolanis Klinik Sehat Setia Brebes. The type of studywas an observational analytic with cross-sectional approach. The sampling technique used in thisstudy was purposive sampling. The subjects of the study were 52 type 2 diabetes mellitus patientsat Prolanis Klinik Sehat Setia Brebes who had met the criteria. The object of this research is thelevel of HbA1c (D-10) and urine microalbumin levels (Architect c8000).The results showed thatthe majority of HbA1c levels were abnormal (>7.0%), which were 38 patients or 73.1%, while themajority of urine microalbumin levels were normal (<30 ug/mg creatinine), which were 31 patientsor 59.6%. The results were analyzed using the Chi-Square test and met the requirements. Theresults were p value = 0.020 < 0.05, the conclusion was that there was a relationship betweenHbA1c and urine microalbumin in patients with type 2 diabetes mellitus at the Prolanis KlinikSehat Setia Brebes